2019
DOI: 10.6007/ijarped/v8-i1/5271
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of Morphological Awareness and Productive Vocabulary Knowledge with Academic Writing

Abstract: The current paper represents a conceptual framework for the relationship between morphological awareness and academic writing directly and indirectly through the mediation of productive vocabulary knowledge. Reviewing the literature guided the researcher in developing the conceptual framework of the current study. The present study suggested a strategy which may help the second language postgraduate students in enhancing their productive vocabulary knowledge regarding the size of words they know and how deep t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Tertiary level students need a good receptive English command to have access to studies and research related to their field of study. They, nevertheless, require good productive academic language knowledge due to the different tasks involved, including dissertations, theses, essays, and tasks [11][12][13]. For language learners, vocabulary is vital for developing language skills and creating meaning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary level students need a good receptive English command to have access to studies and research related to their field of study. They, nevertheless, require good productive academic language knowledge due to the different tasks involved, including dissertations, theses, essays, and tasks [11][12][13]. For language learners, vocabulary is vital for developing language skills and creating meaning.…”
Section: Introductionmentioning
confidence: 99%
“…The development of learners' language relies heavily on vocabulary, so they should expand their vocabulary as they progress by implementing a vocabulary-building strategy that will enable them to overcome the issue of insufficient vocabulary and allow them to succeed in their studies [14]. Having insufficient vocabulary is considered a hurdle to learners' linguistic development and causes problems for their academic success [11], which may be attributed to their poor linguistic awareness, particularly their morphological awareness. Aldawsari [15] revealed that L2 postgraduate students at New Zealand universities had a problem of lack of general and academic vocabulary.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality writing is likely to involve a greater variety of vocabulary, words of varying levels of frequency, and many complex phrases (McNamara, Crossley, & McCarthy, 2009). Academic writing is a very important skill for postgraduate students to master their English language and succeed in their disciplines (Al Badi, 2015;Asaad & Shabdin, 2019a, 2019b. Moreover, it is characterized by morphologically complex words (Nagy & Townsend, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Carlisle, 2016;Dornay, 2017;Kirk & Gillon, 2009). However, the relationship between morphological awareness and academic writing remains unknown (Asaad & Shabdin, 2019a).…”
Section: Introductionmentioning
confidence: 99%